Perbedaan Setting Permainan Bolavoli Antara Elite Atlet Pelajar Indonesia Dan Thailand Pada ASEAN School Games 2019 (Indonesian Journal for Physical Education and Sport, 2021)
The purpose of this research is to find out the differences setting in volleyball games between elite Indonesia team and elite Thailand team at the 11th ASEAN School Games year 2019. This research used qualitative descriptive method with case study approach. The research subjects were the elite athletes of the Indonesian and the Thailand team, totaling 48 athletes. The research instrument using check list (observation method) and documentation method. The data analysis used percentage descriptive. The results of the research shows that Indonesian men team made 117 (66,24%) front direction setting, 143 (61,54%) open spike. Indonesian woman team made 156 (60,58%) front direction setting, 210 (57,38%) open spike. Thailand men team made 126 (61,11%) front direction setting, 205 (63,66%) open spike, Thailand woman team made 178 (67,98%) front direction setting, 197 (64,47%) open spike. Recapitulation setting of Indonesian men team 69,77% good category, Indonesia women team 61,05% good category, Thailand men team 68,42% good category, Thailand women team 69,36% good category. The more effective setting for the men team is more effective the Indonesian men team and for the women team more effective the Thailand women team. The conclusion of this research is direction setting if bait used by the Indonesian and Thailand team men-women of direction of front ball bait. The type of bait that the Indonesian and Thailand team men-women use is a type of open bait ball. The more effective setting for the men team is more effective the Indonesian men team, for the women team more effectively the Thailand women team.